Shelf Life of Hybrid Rice (CORH-2) Seed as Influenced by Stage of Harvest - K. RAJA; A.S. PONNUSWAMY (Seed Research, 2026)
An experiment was conducted at the department of Seed Science and Technology, Tamil Nadu Agricultural University, Coimbatore, India, to know the effect of stage of harvest on storability of rice hybrid CORH-2. The results revealed that the seeds harvested at early stages of 20 and 25 days after 50 per cent flowering lost their viability quickly while, the seeds harvested at 30 and 35 days after 50 per cent flowering retained their viability over a period of 10 months. These results indicated that the seeds (F₁) of rice hybrid CORH 2 harvested at 30-35 days after 50 per cent flowering could be stored for a period of 10 months with minimum loss of vigour and viability as compared to the seeds harvested before 30 and after 35 days after 50 per cent flowering.